Kesiapan Rumah Sakit Dalam Implementasi Sistem Pembayaran Global Budget Di Kabupaten Purworejo - Dina Anjayani; Andreasta Meliala; Yulita Hendrartini (Jurnal Jaminan Kesehatan Nasional, 2022)
In 2018, BPJS Kesehatan initiated a pilot project to integrate the INA CBGs and Global Budget mixed-method hospital payment system (global budget). Purworejo Regency is one of the areas designated as a pilot for the Global Budget payment system's deployment. The outcomes of the Hospital performance indicators in the first-semester review were less than ideal. Consequently, it is required to study the Hospital's readiness to implement the Global budget Payment System. This study set out to determine how prepared the hospitals in Purworejo Regency were to implement the Global Budget payment scheme. A descriptive design and a qualitative methodology were used in the research. The management of four hospitals in Purworejo Regency is the topic of the study.  Observations and interviews were used to explore hospitals’ readiness to implement the Global Budget payment system in terms of health facilities’ perception, Quality Control and Cost Control strategies, Global Budget calculations, and patient satisfaction through the results of the Walk Through Audit.  Through the four key variables mentioned above, the scoring technique is used to evaluate the readiness of hospitals to implement the Global Budget payment system.  The modified CCCEAR (California Community Clinic EHR Evaluation and Readiness) tool is used for the readiness assessment, which has three readiness levels: 1) not ready (score 0-33), 2) moderately ready (34-66), and 3) ready (67-100).  Result:  According to a qualitative examination of data from observations and interviews, the hospital scored 26 from assessor II and 24 from assessor I, positioning it in the second range. This demonstrates that the hospital is not ready and has not considered developing a more comprehensive and in-depth plan for implementing the Global Budget payment system, nor how to create capacity to enable successful adoption and implementation.  Conclusion: The hospital is not yet at its highest level of readiness to adopt the Global Budget payment system in Purworejo Regency, according to the scoring findings on four variables of hospital readiness.